Proof-of-concept, rapid, instrument-free molecular detection of Neisseria gonorrhoeae and ciprofloxacin susceptibility. (26th July 2022) - Ayfan, Abdulrahman K S; Macdonald, Joanne; Irwin, Adam D; Zowawi, Hosam M; Forde, Brian M; Paterson, David L; Lahra, Monica M; Whiley, David M
Abstract: Objectives: To develop instrument-free point-of-care methods using recombinase polymerase amplification (RPA) technology coupled with a simple lateral flow detection system to detect Neisseria gonorrhoeae and susceptibility to ciprofloxacin. Methods: For identification of gonococcal infection, an RPA-based method was developed targeting the gonococcal porA pseudogene (NG- porA -RPA). For ciprofloxacin susceptibility, predictive WT sequences at codons 91 and 95 of the gonococcal gyrA DNase gene were targeted. Given the known complexities of SNP detection using RPA (e.g. the ability to accommodate mismatches) we trialled several different assays incorporating various additional non-template mismatches in the oligonucleotide sequences to reduce affinity for the mutant (resistant) gyrA sequences. Assays were evaluated using a bank of N. gonorrhoeae ( n = 10) and non-gonococcal ( n = 5) isolates and a panel of N. gonorrhoeae nucleic acid amplification test (NAAT)-positive clinical sample extracts ( n = 40). Results: The NG- porA -RPA assay was specific to N. gonorrhoeae and provided a positive percentage agreement (PPA) of 87.5% (35/40) compared with a commercial N. gonorrhoeae NAAT when applied to the 40 clinical sample extracts. For gyrA, the non-template bases successfully reduced banding intensity for double-mutant strains (mutations at both 91 and 95), but not for rarer single-mutant (91 only) strains. The most promising gyrA assay, NG- gyrA -RPA08, correctly detected 83% (25/30) of infections from NAAT-positive clinical samples confirmed to have WT gyrA sequences based on Sanger sequencing. Conclusions: These proof-of-concept data show that RPA technology has considerable promise for detecting N. gonorrhoeae and associated antibiotic susceptibility and would offer a diagnostic-based stewardship strategy identified as urgently needed by the WHO.